Active commuting reduces the risk of wrist fractures in middle-aged women—the UFO study - Englund, U.; Nordström, P.; Nilsson, J.; Hallmans, G.; Svensson, O.; Bergström, U.; Pettersson-Kymmer, U. (Osteoporosis international, 2013)
Summary Middle-aged women with active commuting had significantly lower risk for wrist fracture than women commuting by car/bus. Introduction Our purpose was to investigate whether a physically active lifestyle in middle-aged women was associated with a reduced risk of later sustaining a low-trauma wrist fracture. Methods The Umeå Fracture and Osteoporosis (UFO) study is a population-based nested case–control study investigating associations between lifestyle and fragility fractures. From a cohort of ~35,000 subjects, we identified 376 female wrist fracture cases who had reported data regarding their commuting habits, occupational, and leisure physical activity, before they sustained their fracture. Each fracture case was compared with at least one control drawn from the same cohort and matched for age and week of reporting data, yielding a total of 778 subjects. Mean age at baseline was 54.3 ± 5.8 years, and mean age at fracture was 60.3 ± 5.8 years. Results Conditional logistic regression analysis with adjustments for height, body mass index, smoking, and menopausal status showed that subjects with active commuting (especially walking) were at significantly lower risk of sustaining a wrist fracture (OR 0.48; 95 % CI 0.27–0.88) compared with those who commuted by car or bus. Leisure time activities such as dancing and snow shoveling were also associated with a lower fracture risk, whereas occupational activity, training, and leisure walking or cycling were unrelated to fracture risk. Conclusion This study suggests that active commuting is associated with a lower wrist fracture risk, in middle-aged women.